2015
DOI: 10.3389/fnins.2015.00264
|View full text |Cite
|
Sign up to set email alerts
|

The unfolded protein response in multiple sclerosis

Abstract: The unfolded protein response (UPR) occurs in response to endoplasmic reticulum (ER) stress caused by the accumulation of unfolded or misfolded proteins in the ER. The UPR is comprised of three signaling pathways that promote cytoprotective functions to correct ER stress; however, if ER stress cannot be resolved the UPR results in apoptosis of affected cells. The UPR is an important feature of various human diseases, including multiple sclerosis (MS). Recent studies have shown several components of the UPR are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 134 publications
(203 reference statements)
2
87
0
Order By: Relevance
“…Previous studies have emphasized important roles of PERK signaling in oligodendrocyte survival and remyelination in MS/EAE (Lin and Popko ; Stone and Lin ). It was also recently reported that deletion of GRP78 in oligodendrocytes caused severe impairment in myelination both in physiological and pathological conditions (Hussien et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have emphasized important roles of PERK signaling in oligodendrocyte survival and remyelination in MS/EAE (Lin and Popko ; Stone and Lin ). It was also recently reported that deletion of GRP78 in oligodendrocytes caused severe impairment in myelination both in physiological and pathological conditions (Hussien et al .…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has suggested a crucial role for the UPR in the pathogenesis of various myelin disorders including MS, Pelizaeus–Merzbacher disease (PMD), and their animal models (for review, Lin and Popko ; Stone and Lin ). PMD is an X chromosome ‐linked demyelinating disease which is caused by mutations in the gene proteolipid protein‐1 (PLP1).…”
mentioning
confidence: 99%
“…Although the IRE1 branch is the most conserved part of the UPR, activation of this branch in oligodendrocytes is controversial. Some studies show that the IRE1‐XBP1 pathway is not activated in oligodendrocytes under normal or disease conditions (Hussien et al, ; Stone & Lin, ); however, other studies show opposite results (Mháille et al, ; Ní Fhlathartaigh et al, ; Naughton, McMahon, & FitzGerald, ). A number of studies demonstrate that the PERK branch can positively or negatively influence oligodendrocyte viability in myelin disorders (Southwood, Garbern, Jiang, & Gow, ; Lin, Harding, Ron, & Popko, ; Lin et al, , , ; Hussien, Cavener, & Popko, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, reduced demyelination was also observed. As the blood-CNS barrier is often compromised in neuroinflammatory diseases such as MS or EAE, one can consider a possibility that in addition to reducing inflammatory phenotype of T cells, CX-5461 had also at least some direct beneficial effects on neuroinflammation-challenged oligodendrocytes including attenuation of the cytotoxic ER stress response [25]. …”
Section: Discussionmentioning
confidence: 99%